THE ROLE OF THE POLICE IN EFFORTS TO HANDLE CAROK IN THE TRADITION OF CONFLICT RESOLUTION IN BANGKALAN COMMUNITIES IN MADURA (CASE STUDY IN BANGKALAN POLRES, MADURA) - Deny Frimansyah; Waluyo (Universitas Islam Balitar, 2023)
Indonesia is a country that upholds the principle of the rule of law. State law is something that must be obeyed by everyone without exception. But in the existing reality, state law, especially criminal law, is not enforced on an indigenous community because society has made an existing tradition a law or regulation that is used as an effort to solve problems even though this tradition conflicts with Indonesian criminal law. The Criminal Code (KUHP) is a guide in resolving conflicts that exist in people's lives. In this case, the role of the police as law enforcement officers must be maximized and synergize with the community so that they can adapt to existing traditions in society which in the future are expected to be able to provide a middle way for a conflict between public law, namely criminal law and traditions still held by some circles of society.